Design and experimental verification of composite impact attenuator for racing vehicles. (1st May 2016) - Wang, Jianfeng; Yang, Na; Zhao, Jinghui; Wang, Dafang; Wang, Yongtai; Li, Kun; He, Zhongqing; Wang, Baoming
Abstract: Implementing measures to enhance collision energy absorption of a racing vehicle is essential to protect the vehicle and its driver and maximize the driving performance. In this study, based on the energy absorption characteristics of composites, the requirements of competition rules, and the overall vehicle arrangement, a preliminary design of an impact attenuator is performed. This paper will design the basic model with rules requirement in second section, and refer existing composite material-corrugated beam energy absolved structure, and write in half-corrugated beam energy absolved structure, so the model structure can be parameterize. Based on commercial nonlinear finite element analysis software LS-DYNA, established the numerical model. Subsequently, the optimization is divided into structural and lay-up optimizations. Using the LS-OPT software, and based on the response surface analysis method, the structure is optimized to obtain a composite impact attenuator model with the highest possible specific energy absorption. The lay-up of the model is optimized to attain a final lay-up with the minimum weight. Quasi-static axial compression and dynamic drop-weight impact tests are conducted to verify the optimization design. Finally, the composite impact attenuator of the racing car with high energy absorption efficiency, high specific energy absorption, and light weight is achieved.